Design and Optimization of Rivaroxaban-Cyclodextrin-Polymer Triple Complex Formulation with Improved Solubility - Kang JH; Lee JE; Jeong SJ; Park CW; Kim DW; Weon KY (Dove Medical Press, 2022)
Ji-Hyun Kang,1,* Ji-Eun Lee,1,* So-Jeong Jeong,1 Chun-Woong Park,1 Dong-Wook Kim,2 Kwon-Yeon Weon3 1College of Pharmacy, Chungbuk National University, Cheongju, Korea; 2College of Pharmacy, Wonkwang University, Iksan, Korea; 3College of Pharmacy, Daegu Catholic University, Gyeongsan, Korea*These authors contributed equally to this workCorrespondence: Dong-Wook Kim, College of Pharmacy, Wonkwang University, Iksan, 54538, Korea, Tel +82-63-229-7130, Fax +82-63-850-7309, Email pharmengin@gmail.com Kwon-Yeon Weon, College of Pharmacy, Daegu Catholic University, Gyeongsan, 38430, Korea, Tel +82-53-850-3616, Fax +82-53-850-3602, Email weonky@cu.ac.krPurpose: This study aimed to ensure the convenience of administration and reproducibility of efficacy, regardless of the meal, by improving the solubility of rivaroxaban (RIV).Methods: RIV is a non-vitamin K antagonist oral anticoagulants that exhibits a coagulation effect by directly inhibiting coagulation factor Xa. However, RIV has a very low solubility; therefore, it must be administered with a meal at high doses. We used a drug- hydroxypropyl-beta-cyclodextrin (CD)-water-soluble polymer triple complex (R-C-P complex) to solubilize RIV. Using Minitab, we evaluated the effect of each factor on RIV solubility and developed an optimal R-C-P complex formulation. The amount of CD, amount of polymer, and polymer type were set as the independent variables X1, X2, and X3, respectively. RIV solubility (Y1) and dissolution rate for 45 min in pH 4.5 medium (Y2) and pH 1.2 medium (Y3) were set as response variables.Results: The most efficient RIV solubilization effect was obtained from the composition using CD and HPMC 2208, and physicochemical properties and dissolution parameters were analyzed. RIV in the R-C-P complex was present in an amorphous form and showed high solubility. Unlike commercial products, it showed a 100% dissolution rate. The R-C-P complex formulation secured high RIV solubility and 100% release regardless of pH.Conclusion: The results imply that high-dose RIV can be administered regardless of the meal, reducing the risk of changing the drug effect due to the patient's administration mistake.Keywords: rivaroxaban, drug-cyclodextrin-polymer triple complex, solubilization, design of experiment